Efficacy of fish oil supplementation on metabolic dysfunction-associated steatotic liver disease: a meta-analysis - Zhou, Like; Sun, Dongmei; Bai, Houqiao (Frontiers in Nutrition, 2025)
ObjectiveGlobally, the occurrence of Metabolic dysfunction-associated steatotic liver disease (MASLD) is on a steady rise. Fish oil has anti-inflammatory effects and can improve lipid metabolism. The article aims to assess the impact of fish oil supplementation on MASLD.MethodsWe conducted a systematic search of Cochrane, Embase, PubMed, and Web of Science up to September 31, 2024, for randomized control trials (RCTs). The risk of bias of the included RCTs was evaluated using the Cochrane Collaboration’s tool. Outcomes measured were aspects of liver injury, lipid profile, insulin resistance, anthropometric measurements, and more.ResultsSeven randomized controlled trials (RCTs) involving 439 participants were incorporated into the analysis. In general, the risk of bias in these RCTs was either low or not clearly defined. Pooled analysis showed that triglycerides [TG, pooled standard mean difference (SMD): −0.40 (95% CI: −0.58 to −0.21)], aspartate transaminase [AST, SMD: −0.29 (95% CI: −0.48 to −0.10)], HOMA-IR [SMD: −2.06 (95% CI: −3.36 to −0.49)] and waist circumference [Waist-C, SMD: −0.31 (95% CI: −0.54 to −0.08)] were significantly improved. But showed no significant benefits on alanine transaminase [ALT, SMD: −0.15 (95% CI: −0.45 to 0.15)], gamma-glutamyl transpeptidase [GGT, SMD: −0.07 (95% CI: −0.26 to 0.12)], body mass index [BMI, SMD: 0.16 (95% CI: −0.34 to 0.02)], high-density lipoprotein cholesterol [HDL, SMD: 0.02 (95% CI: −0.18 to 0.22)], low-density lipoprotein cholesterol [LDL, SMD: −0.01 (95% CI: −0.20 to 0.18)], Total Cholesterol [TC, SMD: −0.34 (95% CI: −0.70 to 0.01)] and so on.ConclusionThe current evidence supports the fish oil supplementation in improving MASLD. Fish oil supplementation may also regulate blood lipids and improve glucose metabolism disorders.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier CRD42024513246.